Effect of a diamond-like carbon film on the mechanical and surface properties of microwave-cured polymethylmethacrylate (Research, Society and Development, 2022)
Introduction: Microwave-cured polymethylmethacrylate (MCPM) are commonly used in dentistry due low cost, transparency and easy handling. However, do not have a long useful life, due to their chemical fragility and low hardness and wear resistance. Aim: Assessing the effect of a diamond-like carbon (DLC) film coating on the mechanical and surface properties of MCPM. Methodology: The MCPM samples were divided into control (Gc) and treatment (Gt) groups, and were subjected to flexural strength (n=18), wear resistance (n=18) tests, and to topography and surface roughness (Ra) analysis by three-dimensional optical profilometry (n=18). The films were deposited by plasma-enhanced chemical vapor deposition. Differences between groups were assessed by the Mann-Whitney and t tests using a 5% significance level (p